Differential effects of follistatin on porcine oocyte competence and cumulus cell gene expression in vitro. (14th November 2017) - Guo, Z; Islam, MS; Liu, D; Liu, G; Lv, L; Yang, Y; Fu, B; Wang, L; Liu, Z; He, H; Wu, H
Contents: Several oocyte‐derived genes/proteins are essential to early embryonic development. The expression and stability of these proteins are influenced by the autocrine/paracrine activity of factors released by oocytes and cumulus cells. This study investigated the paracrine and autocrine activity of follistatin (FS), which is secreted by oocytes and cumulus cells as part of porcine embryogenesis. Immunohistochemical (IHC) localization of follistatin was conducted on 100 randomly selected early‐ and late‐cleaving two‐cell embryos. Dissociated cumulus cells were treated with various doses of follistatin for determination of the follistatin gene ( FST ) mRNA expression levels by quantitative real‐time PCR analysis. Microinjection of siRNA induced a downregulation of FST mRNA during embryonic development, thereby decreasing the proportion embryos developing to the blastocyst stage (19.33%). Immunolocalization analysis showed enhanced staining for follistatin in early‐cleavage stage embryos. Quantitative real‐time PCR indicated a significantly lower FST transcript level in cumulus cells after application of the highest dose of follistatin (100 ng/ml). Exogenous follistatin treatment of in vitro maturation embryos resulted in statistically significant dose‐dependent changes during development. Application of the highest concentration (100 ng/ml) of follistatin decreased the maturation rate of the oocytes. On the other hand, the application of 10 ng/ml follistatin resulted in an increase in the number of embryos. The observed differential effect of exogenous follistatin might be due to maternal FST and autocrine/paracrine factors secreted by cumulus cells.